Internalization of Pancasila Values and Nasionalism in Citizenship Education - Kemala, Vinna (Pancasila and Civics Education Journal, 2022)
Historically, education in Indonesia has played an important role in promoting nationalism among Indonesian people. Until now, especially Citizenship Education plays an important and strategic role in preserving, improving, and transforming the values of state ideology and nationalism to the younger generation. In the current era of globalization, Citizenship Education has a mission as education for democracy, politics, multiculturalism, nationalism, and conflict resolution education. Citizenship education must be interpreted maximally , namely teaching students to think critically and analytically in solving social problems and be able to apply the values of state ideology and nationalism. Therefore, civics education is not only taught as transmission citizenship, but also taught as reflective inquiry. To do this, Civic Education must integrate direct or indirect approaches in value education, so that students are able to internalize the values of the state ideology and nationalism as their beliefs. Then, several principles of the maximum teaching and learning process must also color Citizenship Education in Indonesian schools.